"Nihil alieni a me alienum puto". L'alieno e il diverso nello spettacolo UFO Spotykacz di Paweł Passini (Altre Modernità, 2015)
On the basis of the Polish performance from 2009 UFO Spotykacz (UFO Encounter) by the director Paweł Passini, this article presents and analyses how the figure of the alien – unusual for the theatre – became the figure of the Other. Three characters apply to be human being suited to meet an alien; this specific casting situation aiming to find the ideal person who could establish a "close encounter" opens the way to a series of questions about the condition of humanity in general and specifically about the condition of the contemporary society. The Freudian idea of Unheimlich, the theory of Julia Kristeva, and Giorgio Agamben's concept of anthropological machine help to answer to questions such as: is there anyone on Earth who truly represents humanity? and why does the Other – in this case represented by the alien – induce such strong emotions, from interest and desire to fear and hatred? The real meeting between the humans and the alien taking place at the end of the performance reveals only the phobias and frustrations of each character. The silent alien is here a metaphorical window that shows the lack of communication between human beings and the deepest fears of contemporary society.